Dampak Konversi Lahan Pertanian Bagi Taraf Hidup Petani di Kelurahan Landasan Ulin Barat Kecamatan Liang Anggang Kota Banjarbaru - Agung Hadi Hidayat; Usamah Hanafie; Nurmelati Septiana (Universitas Lambung Mangkurat, 2012)
The study is aimed to describe the condition of farmers livelihood before and after land conversion as well as knowing its socio-economic impact. It is a qualitative study, where respondents were purposively selected by using snowball sampling. The results show that the change of farmers’ income before and after land conversion is varied – increase, decrease or no change. Housing and assets ownership has not changed much both before and after the conversion. Health condition is also relatively stable. Land conversion has social and economic impacts as farmers should shift and diversificate their livelihoods on agriculture and non-agriculture sector. The change on household income is depending on the type of new business established. Land conversion also has environmental effect since land conversion for residential area is followed by river backfill which create water flow disturbance.